Maternal Strangulated Diaphragmatic Hernia with Gangrene of the Entire Stomach During Pregnancy: A Case Report and Review of the Recent Literature - Chae AY; Park SY; Bae JH; Jeong SY; Kim JS; Lee JS; Kim SJ; Lee SJ; Lee SH (Dove Medical Press, 2023)
Ah Yeong Chae,1 So Yeon Park,1 Jung Hyun Bae,1 So Yeon Jeong,1 Ji Su Kim,1 Jeong Soo Lee,2 Soo Jin Kim,2 Soo Jeong Lee,3 Sang Hun Lee3 1Department of Obstetrics and Gynecology, University of Ulsan College of Medicine, Asan Medical Center, Seoul, Korea; 2Department of Obstetrics and Gynecology, Eulji University, Nowon Eulji Medical Center, Seoul, Korea; 3Department of Obstetrics and Gynecology, University of Ulsan College of Medicine, Ulsan University Hospital, Ulsan, KoreaCorrespondence: Sang Hun Lee, Department of Obstetrics and Gynecology, Ulsan University Hospital, University of Ulsan College of Medicine, 290-3 Joenha-Dong, Dong-Gu, Ulsan, 682-714, Korea, Tel +82-052-250-8786, Fax +82-052-250-7163, Email shlee73@uuh.ulsan.krBackground: Bochdalek hernia (BH) of congenital diaphragm hernia is infrequently seen in adults. Strangulation of the diaphragm hernia has been recognized as a severe complication. Among several factors, pregnancy is an important cause of diaphragm hernia's deterioration. However, nausea, vomiting, and upper abdominal pain are often considered non-specific pregnancy-related symptoms.Case Presentation: We report a case of a 39-year-old (gravida II, para I) multigravida woman with a delayed diagnosis of strangulated herniated viscera complicating total gastric gangrene at 26+1 weeks' gestation. The preoperative diagnosis was confirmed by an X-ray examination and magnetic resonance imaging (MRI). After identifying the size and severity of the herniated contents through video-assisted thoracoscopy (VAT), we immediately converted to abdominal laparotomy. Antenatal corticosteroids were administered simultaneously with diagnosis to promote fetal maturity. The fetal condition was maintained well in the maternal uterus during the operation. Careful monitoring of the fetus and the mother's clinical conditions should be performed during expectant management to achieve delayed delivery after maternal surgical correction. Delivery was completed through cesarean delivery at 27+1 weeks of gestation.Conclusion: Despite the rarity of maternal Bochdalek hernias during pregnancy, early diagnosis and appropriate treatment via multidisciplinary care are essential for maternal and fetal outcomes.Keywords: strangulation, Bochdalek hernia, pregnancy